Sex-dependent difference in the relationship between adipose-tissue cholesterol efflux and estradiol concentrations in young healthy humans. Issue 64 (February 2018) - Iqbal, Fatima; Durham, William J.; Melhem, Ayyash; Raslan, Saleem; Tran, Tony T.; Wright, Traver J.; Asghar, Rabia; Fujise, Ken; Volpi, Elena; Sidossis, Labros; Abate, Nicola; Sheffield-Moore, Melinda; et al.
Highlights: The prevalence of vascular dementia is higher in men. The prevalence of type 2 diabetes and cardiovascular diseases is higher in men too. High density lipoprotein cholesterol (HDL-C) is lower in men. Adipose tissue cholesterol efflux is important for formation of HDL-C. Sex hormone estrogen maybe a determinant of cholesterol efflux in women but not men. Abstract: Background: Impaired adipose tissue function and lower levels of high density lipoprotein cholesterol (HDL-C) have been implicated in the development of vascular dementia, and metabolic diseases such as hypertension, atherosclerosis, type 2 diabetes (T2D) and metabolic syndrome. Interestingly, both the substrate fluxes in adipose tissue and HDL-C concentration differ between men and women. Moreover, adipose tissue cholesterol efflux has been implicated in modulation of HDL-C levels. Thus, we aimed to determine if the association between serum estradiol levels and adipose tissue cholesterol efflux is sex-dependent. Method: We evaluated the serum estradiol levels and adipose tissue cholesterol efflux in young healthy men (n = 5) and women (n = 3). Adipose tissue cholesterol efflux was determined using subcutaneous microdialysis probes. Linear regression analyses were used to determine the relationship between the parameters, p  < 0.05 was considered as statistically significant. Results: Our data demonstrated that serum estradiol levels directly associated with adipose tissue cholesterol efflux; however, the relationships may be sex-dependent. We discussed our results in the context of currently available data regarding sex-dependent variability in adipose tissue function and HDL-C metabolism as a potential contributor to higher rates of vascular dementia in men. Further research is required to understand the sex-dependent and −independent variabilities in adipose tissue metabolism to determine novel targets for interventions to prevent the development of vascular dementia.